A “Christian Businessman” in the Eastern Townships: The Convergence of Precept and Practice in Nineteenth-Century Evangelical Gender Construction - Van Die, Marguerite (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1999)
AbstractIn their analysis of the impact of nineteenth-century market forces upon the lives of women, historians have drawn attention to the important evangelical construct of the pious, praying mother with its strong, prescriptive norms for female behaviour. This study examines its largely unexplored counterpart, “the Christian businessman”, through means of a detailed case study of the business and family life of a single individual, Charles C. Colby (1827-1907), a prominent Eastern Townships lawyer, entrepreneur, Methodist layman, and federal politician. Richly documented in a large collection of family and business papers, Colby's life offers a unique opportunity to move beyond the clerically constructed “Christian businessman” to a world where business and religious interests were often in daily competition, and where the much-vaunted tranquility of Victorian domestic life was frequently challenged by the forces of the market-place, even in Colby's case, to the point of bankruptcy. The study tests the extent to which an ideal religious construct both influenced and was in tum influenced by the reality of economic and family concerns even as it sought to maintain moral continuity.